DEVELOPING INTEGRATION TECHNIQUES MODULE TO IMPROVE MATHEMATICAL CREATIVE THINKING ABILITY IN INTEGRAL CALCULUS - Titi Solfitri; Hesty Marwani Siregar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to 1) to find out the effectiveness of the integration technique module in integral calculus learning, and 2) to find out the increase in the mathematical creative thinking ability after implementing the integration technique module in integral calculus learning. The development of module was conducted by using ADDIE model with five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were 16 students in the 3rd semester of Mathematics Education Study Program, the Faculty of Teacher Training and Education, Universitas Riau. The research instruments were an expert validation questionnaire, a student response questionnaire, and a mathematical creative thinking ability test. The data obtained were analyzed by using quantitative and qualitative descriptive analysis methods. Based on the results of the validity test, the integration technique module was declared valid and suitable for students to use in the integral calculus course. Judging from the results of the module practicality test, the average percentage of practicality values was 77.8125 and was in the practical category. Referring to the results of the module effectiveness test, the n-gain average of students' mathematical creative thinking abilities was 0.64 and in the medium category. Because the integrated engineering module met the criteria of validity, practicality, and effectiveness, it could be stated that the developed integration technique module improved students' mathematical creative thinking skills in the integral calculus course.